Effectiveness Of Implementing Population Administration Service In Order To Increase Ownership Of E-KTP Documents In Subdistrict Merauke District Merauke - Rachmat, Rachmat Agung; Aenal Fuad Adam; Frederikus Antonius Mana; Syahruddin; Syahrabudin Husein Enala; Muhammad Novan Prasetya (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
Providing services to the community is the main goal of a government agency. One of the services provided is creating E-KTP documents. E-KTP is an update of the conventional KTP which is considered less effective in providing data validity. This E-KTP document can only be owned by one person under one identity, therefore ownership of an E-KTP document is very important to support people's lives. The aim of this research is to find out how effective the implementation of population administration services is in order to increase ownership of E-KTP documents in Merauke District, Merauke Regency. This research uses Emitai Etzioni's effectiveness measurement theory which has four theories, namely: adaptation, integration, member motivation, and production and uses qualitative research methods with a descriptive approach. The data collection technique used in this research is by using field studies and literature studies. The results of the research show that the E-KTP service in Merauke District has been running effectively as indicated by the availability of adequate facilities and the existence of human resources who adapt quickly, however there are still several obstacles in its implementation, namely the failure to disseminate information to the community, limited availability of blanks and still poor employee attitude.